ANALISIS FLEKSIBILITAS EKONOMI MENGGUNAKAN BLACK-SCHOLES-MERTON FORMULA PADA PROYEK TAMBANG BIJIH BESI - Elgi Alam Pangestu; Muhammad Giatman; Murad Murad (Journals Mining Engineering : Bina Tambang, 2018)
The intangible factors in iron ore mining project can be calculated quantitively by using Black-Scholes-Merton Formula. Based on calculation results, NPV value using Discounted Cash Flow (DCF) is obtained that amount Rp. 384.410.329.525. The parameters of Black-Scholes-Merton (BSM) Formula has value amount: Volatility of Commodity Price (σ2)=4,5%, Risk Free Rate (r)=7,61%, Value of Underlying Asset (S)=Rp. 493.178.856.998,86, Capital Budget (K)=Rp. 16.213.165.807, and Loss of Opportunities (γ)=3,28%. So that the value of eNPV is Rp. 539.768.362.897,60 with Option Value (C) amount Rp. 155.358.033.372,49. Sensitivity analysis shows that Option Value (C) is directly proportional to the increment of Value of Underlying Asset (S) and Risk Free Rate (r). Meanwhile the Option Value (C) is inversely proportional to Capital Budget (K), Loss of Opportunities (γ), and Project Time Period (t). The increment Volatility of Commodity Price does not influence Option Value (C).